Memory, history and education around the memory’s grey areas concerning the Spanish Civil War and Francoism - Castillejo Cambra, Emilio (Historia y Memoria de la Educación, 2022)
From certain fragments of the individual memory and the post-memory (both received and inherited) of the author regarding the Spanish Civil War, Francoism and the democratic transition, the objective of this article is twofold. On the one hand, it highlights the need for memory and history to come together, beyond their differences, in the search of the truth. On the other, it points to the need for the dissection of the intricate folds of memory (its fluctuations, its forgetfulness, its silences, its grey areas) to contribute, through the teaching of history, to forming in the students a habit of complex thinking and to train them in the productive use of memory.